Efficacy and safety of Ginkgo biloba extract as an adjuvant in the treatment of Chinese patients with sudden hearing loss: a meta-analysis - Chao Yuan; Huan Zhang; Cuicui Sun; Kai Zhang (Taylor & Francis Group, 2023)
AbstractContext Ginkgo biloba Linn (Ginkgoaceae) [leaves extract (GBE)] is authorized for the treatment of sudden hearing loss (SHL); however, its clinical feasibility in SHL has not been thoroughly investigated.Objective To evaluate the efficacy and safety of adjuvant GBE in the treatment of SHL.Materials and methods We used PubMed, EMBASE, Web of Science, Cochrane Library, China National Knowledge Infrastructure, Wanfang, Chinese Scientific Journal Database, China Biomedical Database for literature research, starting from inception to 30 June 2022. The key terms: Ginkgo biloba extract, Sudden Sensorineural Deafness. This meta-analysis contained randomized controlled trials that compared the safety and efficacy of the combination of GBE and general treatments (GT) with GT alone for SHL. The extracted data were analyzed using Revman5.4 software with risk ratio (RR), 95% confidence intervals (CI) and mean difference (MD).Results Our meta-analysis included 27 articles with a total of 2623 patients. The results revealed that the effects of GBE adjuvant therapy was superior than GT (total effective rate: RR = 1.22, 95% CI: 1.18-1.26, p < 0.00001), the pure tone hearing threshold (MD = 12.29, 95% CI: 11.74-12.85, p < 0.00001) and hemorheology indexes (whole blood high shear viscosity: MD = 1.46, 95% CI: 0.47-2.44, p = 0.004) after treatment were significantly improved compared to non-treatment, while there was no significant difference as for hematocrit (red blood cells) (MD = 4.15, 95% CI: −7.15-15.45, p = 0.47).Conclusion The efficacy of GBE + GT for the treatment of SHL may be more promising than GT alone.